Efficacy Of Mechanical Chest Compression Devices In Cardiac Arrest Management: A Comprehensive Review (The Review of Diabetic Studies, 2025)
Mechanical chest compression devices (MCCDs) are designed to deliver guideline-consistent compressions during cardiopulmonary resuscitation (CPR), potentially overcoming human fatigue, interruptions, and environmental barriers. Over the past two decades, randomized trials and meta-analyses have compared piston (e.g., LUCAS) and load-distributing band devices (e.g., AutoPulse) with high-quality manual CPR across out-of-hospital and in-hospital settings. The aggregate evidence shows no consistent improvement in patient-centered outcomes—return of spontaneous circulation (ROSC), survival to discharge, or favorable neurological status—when MCCDs are used routinely in unselected cardiac arrest. However, MCCDs may confer operational advantages and preserve compression quality during prolonged resuscitations, transport, invasive procedures (e.g., angiography, PCI), hypothermia, and in settings where high-quality manual compressions cannot be reliably maintained (limited staffing, confined spaces, or during airway management and defibrillation charging). Current international guidelines recommend manual CPR as the default and consider MCCDs reasonable in specific circumstances to reduce pauses and maintain high-quality compressions. This review synthesizes device mechanisms, physiologic rationale, comparative effectiveness, safety, implementation considerations, and cost, and proposes a pragmatic framework for selective use. Research priorities include adaptive trial designs for targeted indications, integration with physiologic feedback and ECPR pathways, and standardized reporting of neurologic outcomes and adverse events.